(3TQM aQGFO GdCUhd GdeYQha HGdQSGFd ddCfUGQjs - (3GdfLaj, , GHf cGTa GdZWGA, Ydj Hf eMeO QVG Hf ehSi, J HYO (B1354(3g`s ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3bhdg(B: (3aGYde GdaGA LhGH TQW eMPha JbOjQg CeG HYO aGYde, bhdg(B: (3Gdecda Cbhd Gdecda (B.. (3hgj GdeTbI hdG eTbI aj GdCMcGe GdNeSI EdG aj GdhLhH hGdJMQjes
(3BNQgG (B:s
(3BNQgG(B: (3bdfG de jcf McegG cPGdc Hd JKHJ dgG fJjLI GdHQGFI hfJjLI GdGMJjGW Igj YOe GSJMbGb (B... (3hGSJMbGbg hgPg eSFdI NGQLI Yf GdHMK GdCUhdjs
(3GdfSNI YHGQI Yf eShOI GdeDdas
(3JHUQI GdeDda (B:s
(3PcQ GdRQcdj haGJg SfI (B1350(3g`, ZjQ Cfg cGf MjG SfI (B1354(3, hab eG PcQg eG PcQ aj fgGjI GdLRA GdYGTQ ef cJGH TQM GdcaGjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B5: 19s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3CUhd Gdabgs